Improving the Ability to Write Local Food Posters Using Canva Application in Class XI SMA Negeri 18 Medan - Dapot Hasoloan Bakkara; Panigoran Siburian; Wahyu Ningsih (Prodi PAI STIT Sunan Giri Bima, 2025)
This study aims to improve students' ability to write posters with the theme of local food by utilizing Canva application as learning media in class XI Economics 1 SMA Negeri 18 Medan. The background of this study is based on the low learning outcomes of students in writing posters manually, as well as the lack of utilization of digital technology in the Indonesian language learning process. This research used the Classroom Action Research (PTK) method which was carried out in two cycles. Each cycle includes planning, implementation, observation, and reflection stages. Data were collected through observation, questionnaires, interviews, and learning outcome tests. The results showed that the use of Canva significantly increased students' average score from 73.34 in the pre-action stage to 81 in cycle I, and increased again to 90 in cycle II. Learning completeness also increased from 51% to 80%, then reached 100% in cycle II. In addition to cognitive improvement, the use of Canva also encouraged creativity, active participation, and student learning motivation. These results show that the integration of Canva application in Indonesian language learning is effective for developing students' visual writing skills as well as supporting character strengthening in accordance with the Pancasila Student Profile.